3(9y+3)-9=2y+21

Simple and best practice solution for 3(9y+3)-9=2y+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(9y+3)-9=2y+21 equation:


Simplifying
3(9y + 3) + -9 = 2y + 21

Reorder the terms:
3(3 + 9y) + -9 = 2y + 21
(3 * 3 + 9y * 3) + -9 = 2y + 21
(9 + 27y) + -9 = 2y + 21

Reorder the terms:
9 + -9 + 27y = 2y + 21

Combine like terms: 9 + -9 = 0
0 + 27y = 2y + 21
27y = 2y + 21

Reorder the terms:
27y = 21 + 2y

Solving
27y = 21 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
27y + -2y = 21 + 2y + -2y

Combine like terms: 27y + -2y = 25y
25y = 21 + 2y + -2y

Combine like terms: 2y + -2y = 0
25y = 21 + 0
25y = 21

Divide each side by '25'.
y = 0.84

Simplifying
y = 0.84

See similar equations:

| 39+0.75x=x | | (4z+2)+(5z-3)= | | T*4-3=12 | | 5x^2+10x+46=0 | | 14=-0.5x^2+46 | | 3(4x-1)=9x+6 | | 18x-6=20x-12 | | A*5+6=10 | | -30de+12=18d | | 5t+6-2r=7r-10 | | y+9x^3y=0 | | 4x+1=4x-2 | | 3x-5x+3=x-7+10 | | -5(x+2)+3x=-5(x-3)+3x | | 70x^3+112x-1=0 | | 108=-6(x-8)-4x | | 7n=50+24 | | Y-3=-(x-5) | | (5x+y)+(2x+6y)= | | 2(x+9)=26 | | 3*8x=1.5e^2x | | x^4+0.5x^3-6x^2+5=0 | | g-(-7)=13 | | 33=6a+2 | | 20p-(7+2p)= | | z^2+(4+2i)z+(2-3i)=0 | | 39-15y=-31-5y | | 21y^14-7y^4=0 | | 2y-4x=-3-2x+y | | 8x-5=63 | | (3.2+1)-(0.6*7)= | | Logx(256)=2 |

Equations solver categories